Studi Penggunaan Obat Phenytoin Kurang dari Tiga Bulan terhadap Kadar Magnesium Serum dan Jumlah Kejang Pasien Epilepsi di RSUD DR. Soetomo Surabaya - Sanjiwani, Kadek Siska Febri; Sugianto, Paulus; Kasih, Elisabeth (Jurnal Farmasi Sains dan Terapan, 2017)
Epilepsy is a clinical phenomenon associated with an electrical explosion or excessive abnormal depolarization, which occurs in focus in the brain which causes a paroxysmal awakening. One of the anti-epilepsy drugs is phenytoin which belongs to the hydantoin class. This study aims to describe the serum Mg levels in epilepsy patients with phenytoin drug therapy in Dr. Soetomo General Hospital with a treatment period of less than three months and to identify DRP problems (Drug Related Problems). The method used in this study is prospectively presented by descriptive method (observational). The population in this study were epilepsy patients who were treated at the RSUD dr. Soetomo Surabaya with a sample of 28 epilepsy patients treated at the Outpatient and EEG Neurology Room at Dr. Soetomo General Hospital Surabaya. Results showed that Mg2+ levels in 28 patients with the highest magnesium levels were 2.46 mg / dL. While the lowest magnesium content is 1.78 mg / dL. Conclusions Patients' magnesium levels are still within the normal range but it has not been concluded that phenytoin can increase serum Mg2+ levels and there is no significant difference between phenytoin therapy in epilepsy patients